2010
DOI: 10.1007/s10897-009-9275-3
|View full text |Cite
|
Sign up to set email alerts
|

Parental Decisions Regarding a Prenatally Detected Fetal Chromosomal Abnormality and the Impact of Genetic Counseling: An Analysis of 38 Cases with Aneuploidy in Southeast Turkey

Abstract: This study investigated parental decision-making to terminate or continue a pregnancy after prenatal diagnosis of a chromosomal abnormality among a sample of patients in Southeast Turkey. Between 2004 and 2007, 1068 amniocentesis tests were performed in the Medical Biology and Genetic Department Laboratory at Dicle University. Aneuploidy was found in 38 cases (3.56%). Genetic counseling was provided for the couples that received abnormal results, and they were later interviewed and asked if they had continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 18 publications
3
34
0
2
Order By: Relevance
“…Research by Quadrelli et al, 26 for instance, examined 52 SCA diagnoses in the genetic unit of the Hospital Italiano in Uruguay and reported that women of young maternal age (mean = 32.6 ± 5.2 years) were more likely to terminate their pregnancy compared with those who were older (mean = 36.4 ± 4.4 years). The study conducted by Balkan et al 29 also revealed that women who were of younger maternal age (mean = 32.6 ± 6.7 years) elected to terminate their pregnancies at higher rates than older women (mean = 35.4 ± 5.3 years). Hamamy et al, 8 however, reported in their study that women would be more likely to terminate the pregnancy if their age was 36.8 years (older maternal age).…”
Section: Parents' Age As a Termination Factormentioning
confidence: 94%
See 4 more Smart Citations
“…Research by Quadrelli et al, 26 for instance, examined 52 SCA diagnoses in the genetic unit of the Hospital Italiano in Uruguay and reported that women of young maternal age (mean = 32.6 ± 5.2 years) were more likely to terminate their pregnancy compared with those who were older (mean = 36.4 ± 4.4 years). The study conducted by Balkan et al 29 also revealed that women who were of younger maternal age (mean = 32.6 ± 6.7 years) elected to terminate their pregnancies at higher rates than older women (mean = 35.4 ± 5.3 years). Hamamy et al, 8 however, reported in their study that women would be more likely to terminate the pregnancy if their age was 36.8 years (older maternal age).…”
Section: Parents' Age As a Termination Factormentioning
confidence: 94%
“…Descriptive data: Type of SCA represented the most frequent factor associated with terminating a pregnancy, identified in more than half of the reviewed studies (57.9%). 3,[8][9][10]18,20,22,23,[27][28][29] Two specific types of SCAs, 45,X (Turner syndrome) and 47,XXY (Klinefelter syndrome), in particular, were associated with termination. Nine studies (47.4%) [8][9][10]18,20,23,[27][28][29] indicated that parents with a Turner syndrome-affected fetus would be more likely to terminate the pregnancy, with an average termination rate of 76% (range: 33-100%).…”
Section: Studies' Findingsmentioning
confidence: 99%
See 3 more Smart Citations